ANALISIS KADAR CL PADA SUMUR SG-12 DAN SG-18 DAERAH CILODONG DAN SEKITARNYA EKCAMATAN CILODONG KOTA DEPOK PROVINSI JAWA BARAT - Muhammad Alvin Kurniawan; Abdurrahman Assegaf; Dewi Syavitri (Universitas trisakti, 2022)
This Research was conducted in the Cilodong area and its surroundings, Cilodong district, Depok, West Java. The geology in this research area consists of Qa (alluvium), Qav ( alluvium fan), and Qv (young volcanic unit). The groundwater level in this study area ranged from 76.2-86.14 dml. This research area has a high Cl (chloride) value with a minimum value of 11,846 mg/l at SG-12 and a maximum value of 70,517 mg/l at SG-19. The difference in Cl (chloride) levels is also supported by differences in the study area such as TDS values of 40 mg/l at SG-12 and 200 mg/l at SG-18 and EC of 40 µmhos/cm at SG-12 and 400 µmhos/cm at SG-18.